International Security Relations in the Euro-Atlantic Region in the Late 1990s (Czech Journal of International Relations, 1999)
The development of international security relations following the end of the Cold War was marked by a precedence of positive tendencies over negative trends. Bipolar confrontation and the threat of conflict disappeared, and relations began to develop towards dialogue, cooperation and integration. Joint security as well as general security became the characteristic features of the new security environment. But new risks emerged, linked, above all, with the proliferation of weapons of mass destruction, terrorism, organized crime, nationalism, instability and economic upheavals. Economic crises confirmed that the markets control governments and that the fluctuations of these markets can lead to political destabilization. The emergence of a new category of nuclear powers underscored the risk of underestimating the nuclear deterrent.Since the mid-1990s, the US has intensified its trend of uncompromising action. Its policy confirmed that at the global level a struggle for power is once again in progress. The US systematically improved its military capacity, increased its share in the worldwide export of arms, took advantage of the facilities of the World Bank and the International Monetary Fund, and acted in a most uncompromising manner vis-à-vis the UN. The primary instruments of the American policy of global unilateralism were economic sanctions and military intervention.We can assess the Yugoslav crisis as the most serious problem of the entire post-confrontational period at three major levels. First, it revived historical reminiscences connected with mutual injustices between Serbs and Croats. Then there is the level of cultural nationalism, the escalation of which led to the rise of national security dilemmas between Serbs and Croats. The third level is the behaviour of the most influential protagonists of international relations. Germany, the US and gradually even NATO as a whole took a firm stand on the side of the Croats. We can assess developments in Kosovo in the same way. Here, too, historical reminiscences came to the fore with the result of a maximum escalation of the national security dilemma between Serbs and Albanians. The international community again sided against the Serbs. There was a predominant view that the Kosovo crisis cannot be judged as a purely internal affair. The Allied Force campaign was a solution by force. But the question is, how long will it guarantee stability in the Balkan region?Military intervention cannot be mistaken for humanitarian activities, even though NATO has defined itself as the central institution of a new architecture of European security, and the importance of military security instruments again came to the forefront in its strategy. The domination of the US became further pronounced within NATO. Yet it can be expected that after a certain slow-down, cooperation between NATO and the US on the one hand, and Russia on the other, will continue.